The Paradox of Nickel Mining and Indigenous Peoples’ Rights in Raja Ampat - Adinda Rachman; Nadir Nadir; Win Yuli Wardani (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The expansion of nickel mining in the Raja Ampat Islands has generated tensions among the green energy transition agenda, biodiversity conservation, and the rights of Indigenous Papuan communities. This study aims to analyze the national and international legal frameworks governing the Indonesian government’s obligations, evaluate the extent to which these obligations have been fulfilled in the governance of mining activities in Raja Ampat, and formulate a multidimensional legal accountability framework for the protection of Indigenous peoples. The study employs a normative legal research method using statutory, conceptual, case, and comparative approaches, with qualitative analysis of the collected legal materials. The findings reveal that, although Indonesia possesses an adequate normative framework, its implementation is hindered by significant accountability deficits, including policy inconsistencies, limited participation of Indigenous communities, and ineffective enforcement of environmental laws. This study proposes a model of administrative, constitutional, civil, environmental, and human rights accountability as a foundation for reforming mining governance toward ecological justice, the protection of Indigenous communities, and the sustainable management of natural resources.